Improving the local thermal conductivity of flexible films by microchannels filled with graphene. (June 2021) - Gao, Min; Peng, Kai; Pan, Taisong; Long, Fei; Lin, Yuan
Abstract: Low thermal conductivity is an outstanding problem that hinders the application of polymer substrates in flexible devices. Incorporating high thermal conductivity fillers into polymer to enhance its thermal conductivity usually requires a large mass fraction of fillers at the expense of the flexibility and the insulation capabilities of polymer substrates. The non-uniform heat distribution in flexible devices allows for improving the local thermal conductivity of the core areas via microchannels, a strategy which is an effective method in thermal engineering and can be well designed to adapt to large deformation of flexible devices. Here, we report the fabrication of microchannels in polyimide (PI) composite film by oxygen plasma etching and subsequent filling the microchannels with graphene. Utilizing the time-domain thermoreflectance method and the finite element method, we confirmed that the local thermal conductivity of graphene-filled region is about 10 times larger than that of the unfilled region, which is comparable to that of the PI composite filled heavily with traditional high thermal conductive fillers. In addition, it was also found that stretching the film did not lower the thermal conductivity of the same region. Highlights: Fabricating microchannels filled with graphene in a thin polyimide film. Ten-fold increase in the local thermal conductivity of graphene-filled region. An effective method to improve the local thermal conductivity of flexible substrates.